2018
DOI: 10.3389/fpsyt.2018.00444
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Anxiety and Body Representation in Anorexia Nervosa

Abstract: Individuals with anorexia nervosa (AN) typically display anxious traits prior to the onset of food avoidance and weight loss that characterize the disorder. Meal associated anxiety is an especially common clinical feature in these patients, and heightened sensitivity to sympathetically mediated interoceptive sensations has also been observed. However, it remains unclear how heightened interoceptive sensitivity relates to experiences of anxiety before and after meals. To investigate this relationship, we experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 63 publications
4
54
0
Order By: Relevance
“…Significantly, these studies similarly found no difference in interoceptive accuracy, but did find prediction errors made specifically in the context of meal anticipation. This appeared to be related to heightened anxiety, and atypical interoceptive representation of the heartbeat: individuals with AN located sensations in the left side of their chest in the absence of actual stimulation (56). Further research should consider exploring aspects of interoception in AN other than accuracy, including the ability to discriminate between sensations, or magnitude estimations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Significantly, these studies similarly found no difference in interoceptive accuracy, but did find prediction errors made specifically in the context of meal anticipation. This appeared to be related to heightened anxiety, and atypical interoceptive representation of the heartbeat: individuals with AN located sensations in the left side of their chest in the absence of actual stimulation (56). Further research should consider exploring aspects of interoception in AN other than accuracy, including the ability to discriminate between sensations, or magnitude estimations.…”
Section: Discussionmentioning
confidence: 98%
“…If individuals with AN have less confidence in their ability to detect interoceptive sensations, this could result in a reliance on other cues, such as prior beliefs around likely interoceptive responses. The possibility that people with AN rely on predicted sensations, as opposed to the detection of actual sensations, is supported by research suggesting that people with AN find it difficult to detect actual interoceptive responses from anticipated responses (55,56). Individuals with AN were more likely to falsely endorse changes in interoceptive sensation in the absence of stimulation, and reported more intense cardiorespiratory sensations compared to HC, during pre-meal states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the term interoception is now employed more precisely to distinguish the various phases at which an individual can sense, interpret, and integrate visceral sensations into adaptive actions (Khalsa et al, ), this earlier conceptualization of low interoception has been documented as a nonspecific, variable risk factor of low to medium effect (Jacobi et al, ). More recently, controlled laboratory studies verified that in ambiguous conditions, individuals with AN have difficulty discriminating adaptive visceral signals from false alarms and experience “visceral illusions” that indicate decreased body awareness (Khalsa et al, ; Khalsa et al, ). Thus our conceptualization adds to this body of evidence by highlighting the potential importance of early GI events as contributing to subsequent somatic avoidance and confusion.Hypothesis Early GI events may increase vulnerability to the development of a fear of weight gain specifically and dangerous weight‐loss behaviors that have the added motivation of altering GI experience.…”
Section: Introductionmentioning
confidence: 98%
“…During low arousal states, participants mostly felt their heartbeats in the lower left chest. Some participants also reported heartbeat sensations in the head, neck, belly and arms (Hassanpour et al 2016;Khalsa et al 2018;. Good heartbeat perceivers, based on how accurately they performed the heartbeat detection 'counting' task (in which the reported number of 'felt' heartbeats, counted over different time periods are compared to veridical heartbeats, measured using ECG) report more spontaneous sensations (SPS; e.g.…”
Section: Introductionmentioning
confidence: 99%